Intra-Ampullary Papillary-Tubular Neoplasm: An Update on the Ampullary Counterparts of Pancreatobiliary Intraductal Neoplasms - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2018)
Intra-ampullary papillary tubular neoplasms (IAPNs) are papillary or polypoid lesions that originate from and grow predominantly within the ampulla. They are fundamentally adenoma-carcinoma sequence and as such represent intra-ampullary counterparts of other tumoral intraepithelial neoplasms of the pancreatobiliary tract, namely, intraductal papillary mucinous neoplasms (of pancreas), intraductal papillary neoplasms (of bile ducts), intraductal tubulopapillary neoplasms (ITPNs) (of bile ducts and pancreas), and intracholecystic papillary tubular neoplasms (of gallbladder). Intra-ampullary papillary tubular neoplasm-associated invasive carcinoma is now recognized as a distinct subset among ampullary cancers in the College of American Pathologists synoptic reporting. Intra-ampullary papillary tubular neoplasms show a spectrum of neoplastic change from low grade to high grade. Most cases, however, are associated with high-grade dysplasia, and a significant proportion (similar to 75%), also with invasive carcinoma (usually small, often <1 cm). Unlike intraductal papillary mucinous neoplasms of the pancreas and intestinal-type adenomas of ampullary duodenum, IAPNs often display a mixture of cell lineages and chimeric appearance, but some cases are predominantly gastropancreatobiliary or intestinal type. Intra-ampullary papillary tubular neoplasms may exhibit papillary, tubular, or tubulopapillary growth patterns in variable amounts. They were recognized in the World Health Organization 2010 classification under 2 separate groups, intestinal adenoma versus noninvasive papillary neoplasms, but because of the overlap between these 2 groups, and also the presence of other patterns like tubulopapillary and gastric-lineage types, a unifying category of IAPN was created. They often get classified indiscriminately as ampullary adenocarcinoma, although their biology and behavior are substantially different than other subsets of ampullary carcinomas. The size of invasive carcinoma ought to be reported separately, and T staging of the tumor is to be based on the invasive component. In conclusion, IAPN shows many analogies to intraductal neoplasia of the pancreatobiliary tract and intracholecystic tumors, but at the same time it forms a pathologically and biologically distinct entity among ampullary neoplasms.
Keywords: ampulla; ampullary carcinoma; intra-ampullary papillary-tubular neoplasm; PERIAMPULLARY ADENOCARCINOMAS; HISTOLOGIC TYPE; BILE-DUCTS; CARCINOMAS; CLASSIFICATION; VATER; SURVIVAL; BILIARY; DIFFERENTIATION; ASSOCIATION